OTULIN maintains skin homeostasis by controlling keratinocyte death and stem cell identity - Esther Hoste (Nature Portfolio, 2021)
OTULIN is a deubiquitinase for linear ubiquitin chains. Here the authors show, using genetic mouse models and single-cell RNA-sequencing, that deficiency of OTULIN in keratinocytes causes skin inflammation and verrucous carcinoma via the induction of keratinocyte death, thereby implicating a function of OTULIN in keratinocyte homeostasis.